THE IMPACT OF COLONIALISM ON THE POLITICS OF CAMEROON (PANGEEA, 2025)
The 1884-1885 Berlin Conference was a gathering of European nations that aimed to establish territorial boundaries and mitigate potential conflicts in the pursuit of colonialism. The European colonization of Africa had a profound impact on the political consciousness of the African population, which was essential for the continent's advancement. Colonial institutions have significantly affected the political atmosphere that has emerged in the aftermath of independence. This article employs a historical methodology and conducts a thorough review of multiple types of empirical literature and materials to examine the impact of colonialism on Cameroon's politics. This paper examines the political administrative strategies of colonial administrations in Cameroon and their impact on political development, emphasizing the significance of colonialism in understanding the current political climate in Cameroon. The German colonization of Cameroon commenced in the 1880s and concluded with the signing of the Treaty of Versailles in 1919. After World War I, Germany lost its colonial territory in Cameroon, and Cameroon was partitioned into French and British trust territories. The French colonizers in Cameroon implemented the policy of assimilation, which compelled Cameroonians to adhere to the French cultural norms and beliefs. Cameroonians who had integrated into French society were acknowledged as members of the French community, notwithstanding the restricted access to education. Governors of British colonies claimed that although Cameroonians were not political allies of the British, they were expressing political power in the nation. The British administrative approach of indirect rule permitted only Cameroonians to exercise political authority over their compatriots. The discourse concerning the influence of colonization on Cameroonian politics endures. Some argue that it led to resource depletion, labor exploitation, and cultural ruin, while others assert that it improved Cameroonian politics. The study found that the three colonial governments that imposed their policies on Cameroon have had impacts on the nation's politics and philosophy, resulting in a sacrifice of their own values and traditions. As a result, a Western-style political framework has disregarded local perspectives and political ideas.
Keywords: Colonialism; Direct Governance; Assimilation; Indirect Rule; Cameroon politics